2003
DOI: 10.1080/00288233.2003.9513555
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of soil fluorine: Its impact on the fluorine metabolism and status of grazing young sheep

Abstract: When young sheep ingested soil fluorine (F) at moderate to high rates (69-184 mg F day-1 for 63 days) the apparent absorption of F ranged from 44 to 53%, while apparent retention of F ranged from 28 to 42%. The respective values for ingestion of sodium fluoride (NaF) at 69 mg F day-1 were 69% and 39-45%. Increasing F intakes had little effect on kidney and liver F concentrations, but markedly increased the bone F concentrations in the sheep fed NaF or soil with high levels of F. Further, serum F concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The F t concentration range of 212–617 µg g −1 soil is similar to that of 217–454 µg g −1 soil previously obtained for another set of New Zealand pasture topsoils (0–75 mm depth) (Loganathan et al ., 2001). At normal soil ingestion rates, soils with these F concentrations are unlikely to cause F toxicity to grazing animals (Grace et al ., 2003). The F water and F KCl concentrations were approximately equal for each soil and they were nearly two orders of magnitude less than the F t concentrations (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The F t concentration range of 212–617 µg g −1 soil is similar to that of 217–454 µg g −1 soil previously obtained for another set of New Zealand pasture topsoils (0–75 mm depth) (Loganathan et al ., 2001). At normal soil ingestion rates, soils with these F concentrations are unlikely to cause F toxicity to grazing animals (Grace et al ., 2003). The F water and F KCl concentrations were approximately equal for each soil and they were nearly two orders of magnitude less than the F t concentrations (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Large rates of ingestion of soil with elevated F concentration have potential to cause chronic fluorosis in grazing animals (Cronin et al ., 2000; McLaughlin et al ., 2001). However, a soil‐F ingestion study on grazing young sheep showed that chronic fluorosis is unlikely to occur in most New Zealand pastoral conditions at current soil F concentrations (Grace et al ., 2003), but remains a concern if soil F continues to accumulate. If the solubility of F in soil is excessive it can also affect plant growth (Stevens et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In this trial, young sheep (14 mon old) were fed daily with lucerne (7 mg F/kg dry matter) or lucerne plus soil (184 mg F/kg dry matter) daily for 63 d. The blood F concentration Grace et al (2003). in sheep fed with soil increased signifi cantly within 23 d and then remained constant up to 55 d (Fig. 14).…”
Section: B Fluorinementioning
confidence: 99%
“…The soil used in this study was a Yellow-grey earth (Pallic Soil) (Hewitt 1993), collected from a depth of 0-5 cm, at two sites, 10-20 and 200 m from a fertiliser bin next to an air strip on a Manawatu sheep farm in New Zealand. The soil from this site was previously used for a sheep F ingestion study, and has been described by Grace et al (2003). The soil samples had F concentrations of 1452 and 336 mg F kg -1 air dried soil at the 10-20 and 200 m sites, respectively.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The animals were slaughtered at day 64 and the right metacarpus removed, defleshed, weighed, dried at 100°C for 24 h, and DM determined. The methods of sampling have been described by Grace et al (2003).…”
Section: Sampling Of Blood and Bonementioning
confidence: 99%